Use of a Reinforcing Module to Maintain Linguistically-Oriented Attitudes - McCaleb, Joseph L. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Research studies indicate that beginning teachers choose instructional procedures which conflict with their methods courses and that language is the least well-taught of the English instruction components. To deal with both problems in teacher preparation, a study was devised to analyze the effects of a reinforcing module in language instruction, designed to maintain linguistically-oriented teaching attitudes in student teachers who had a background of two or more courses in linguistics. For the study, the 55 student teachers supervised through the English education office of a university participated in one of three self-instructional modules: persuasion in the English class, media study, or language instruction (the experimental condition). All of the modules required students to respond to a simulated problem by preparing both written responses to specific questions and an audio-taped response to the situation. Attitude changes were assessed through a modified version of the Language Inquiry developed by Ellen Frogner (1969). Results indicated that student teaching, in general, was not conducive to the maintenance of linguistically-oriented attitudes, and that, while course work in language studies develops these attitudes, the experimental module presented at the same time as student teaching provided adequate reinforcement of linguistically-oriented attitudes. (MAI)
ERIC Note: Research prepared at the University of Maryland.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Educational Research; English Education; English Instruction; Higher Education; Language Attitudes; Language Instruction; Language Research; Linguistic Theory; Positive Reinforcement; Program Effectiveness; Student Teachers; Teacher Education; Reports, Research